A Study of Qura nic Prayers - amir hamzeh salar zai (پژوهش نامه معارف قرآنی, 2013)
The author of this paper seeks to prove by means of descriptive- analytic method and library researches that the Qura nic prayers are so delicate that the non-Qura nic prayers recited by the prophets and saints lag seriously behind them. The results demonstrate that the Qura nic prayers open with words markedly different from those of non-Qura nic ones; therefore, those non-Qura nic prayers in which God, against His divine dignity and omniscience, is addressed by words other than Rabb are open to suspicion.